Airborne microplastics: a review study on method for analysis, occurrence, movement and risks - Enyoh, Christian Ebere; Verla, Andrew Wirnkor; Verla, Evelyn Ngozi; Ibe, Francis Chizoruo; Amaobi, Collins Emeka (Environmental monitoring and assessment, 2019)
Microplastics (of size < 5 mm) pollution in our environment is of current concern by researchers, public media and non-governmental organizations. Implications by their presence in aquatic and soil ecosystems have been well studied and documented, but less attention has been paid on airborne microplastics (MPs). Studies concerning airborne microplastics started from 2016 and only a few ( n = 13) have been published to date. Although, studies may increase in the following years, since air is very important for human survival. Microplastics have been observed in atmospheric fallouts in indoor and outdoor environments using a sampling or vacuum pump, rain sampler, and/or particulate fallout collector. Identification and quantification have been carried out by visual, spectroscopic, and spectrometric techniques. Factors such as meteorological, climatic, and anthropogenic influence the distribution and movement of airborne MP. Human exposure may be through inhalation, dermal, and open meal during fallout, with their potential biopersistence and translocation. Ingestion may cause localized inflammation and cancer due to responses by the immune cells, especially in individuals with compromised metabolism and poor clearance mechanisms. Ecological risks involve possible contamination of the ecosystem through a dynamic relationship of MPs in soil, water, and air forming a MP contamination cycle. The present review aimed at providing a comprehensive overview of current knowledge or information regarding microplastics in air, identifying gap in knowledge, and giving suggestions for future research.